The Effect of Compensation, Work Discipline, Work Environment, and Psychological Workload on Employee Performance: Evidence from Kiyo Coffee Shop, Bandar Lampung - Bayu Adi Pratama; Daffa Satrio; Farhan Achmad Satria; Febrianty Febrianty; Reza Hardian Pratama (International Journal of Business, Law, and Education, 2026)
Employee performance is a central determinant of service quality and customer experience in the coffee shop sector, where employees are required to deliver products accurately, respond to customers promptly, and maintain service consistency under time pressure. This study examines the effects of compensation, work discipline, work environment, and psychological workload on employee performance at Kiyo Coffee Shop Pramuka, Bandar Lampung. A quantitative explanatory design was employed using a census approach involving all available employees. Data were collected through structured questionnaires developed from established human resource management and occupational psychology constructs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model demonstrated acceptable convergent validity, with indicator loadings ranging from 0.724 to 0.920 and Average Variance Extracted values exceeding 0.50 for all constructs. The structural model showed strong explanatory power, with an adjusted R-square of 0.897 for employee performance. The results reveal that the work environment has a positive and statistically significant effect on employee performance (β = 0.470; t = 2.836; p = 0.005). Compensation has a positive but non-significant effect (β = 0.396; p = 0.076), work discipline has a positive but non-significant effect (β = 0.102; p = 0.509), and psychological workload has a negative but non-significant effect (β = -0.047; p = 0.808). These findings indicate that, in a small-scale coffee shop context, the work environment is the most salient managerial lever for improving employee performance. The study contributes to human resource management literature by contextualizing performance determinants in a local hospitality microbusiness setting and offers practical implications for improving workplace facilities, interpersonal relations, leadership support, and workload management.